Endoscopic role of problems in dentistry surgery: A review (Texas Journal of Medical Science, 2022)
There are descriptions of clinical procedures that take place inside the oral cavity that may be found in published medical literature. These treatments may use dental instruments and materials. The usual operations of dentistry and medicine are increasingly including the swallowing and aspiration of foreign substances. In particular, the ingestion and aspiration of foreign substances is becoming more commonplace. Although accidental consumption of dental equipment is less of a medical emergency than its more serious counterpart, aspiration, there is no guarantee of a favorable outcome. Aspirations significantly increase the risk of passing away. When it comes to treatment for difficult issues, the majority of the time, medical intervention in the form of endoscopic or surgical treatments is necessary. The goal of this study is to conduct a literature review with the goals of identifying the subspecialties of dentistry that are most likely to be involved in cases of accidental ingestion of dental instruments and to highlight the significant role that endoscopy plays in precisely locating and removing foreign bodies. The review of the literature will be conducted with the intention of identifying the subspecialties of dentistry that are most likely to be involved in cases of accidental ingestion of dental instruments. It has become clear that the dental subspecialties of prosthodontics, operative dentistry, orthodontics, and maxillofacial surgery are the ones in which the incidence of such errors occurs the most frequently. Given this information, ordinary dentists and specialists alike need to be aware of the necessary precautions to take in order to prevent clinical incidents of this nature. Additionally, in order to be able to overcome these problems during the course of ordinary dental procedures, they need to be conversant with the instruments that are accessible, such as endoscopy